Connotation, research status, and development directions of clean coal geology in China - Yuegang TANG; Shaoqing WANG; Xiaoshuai WANG; Xin GUO; Yafeng WANG; Liping XUE; Harold H. Schobert (Meitian dizhi yu kantan)
[Objective] The exploration and assessment of low-carbon, zero-emission, and maximized utilization of coal resources, emerge as a focus of coal geology in the 21st century. [Research Advances] Based on the research content of coals and coal geology, along with the domestic and international development trends of clean coal technology (CCT), this study defines clean coal geology in the broad and narrow sense. Clean coal geology in the narrow sense focuses on the geological and geochemical issues related to efficiency enhancement and emission reduction in coal processing and utilization. In contrast, clean coal geology in the broad sense emphasizes efficiency enhancement and emission reduction throughout the coal life cycle, involving the exploration, exploitation, and utilization of coals, as well as relevant ecological restoration. This study summarizes the compositions and distributions of beneficial and harmful components in coals and analyzes the geologic factors affecting CCT, which are primarily associated with endogenetic and exogenetic geological processes during coal formation and involve tectonics, metamorphism, volcanic eruption, magmatic intrusion, aeolian-fluvial transport and deposition, redox reactions, and groundwater. Furthermore, this study provides a comprehensive overview of the current status of research on the clean assessment, clean processing, conversion, and utilization of coal resources. Additionally, this study reviews the advances in research on China's clean coal geology, categorizing them into five stages: germination, exploration, maturity, establishment, and expansion. [Issues and Prospects] This study proposes some scientific and technical problems concerning coal formation, organic/inorganic elements, minerals, and clean assessment, positing that future advancements in chemistry, physics, biology, and big data/artificial intelligence (AI) will bring opportunities for the further development of clean coal geology and its applications in large-scale engineering. In the next decade, important research and development directions will include the spatiotemporal distribution of clean coals; the green, intelligent, quality-based combined production of paragenetic and associated minerals like coal gas; clean coal gasification; coal-based novel materials; underground coal-to-chemicals, and ecological restoration. It is advisable to continuously pay attention to the innovative research achievements in these aspects.